The Progressive Failure Mechanism of the Tunnel-Slope System under Rainfall: An Experimental Investigation. (22nd September 2022) - Jiao, Qinglei; Wang, Yingchao; Jiang, Wen
Abstract : Tunnel excavation has always been an important reason for the stability failure of the tunnel-slope system at the portal section. In case of rainfall, it is likely to cause serious disasters such as tunnel vault collapse, water inrush from the tunnel face, and slope slip. In this study, the Sunjiaya tunnel of the Daping slope group was taken as the engineering background, and the tunnel model experiment system under the condition of rainfall and groundwater seepage was designed independently to explore the failure laws of slope instability induced by tunnel excavation under the condition of rainfall. Meanwhile, a fiber grating monitoring system was also used to measure the displacement, water content, earth pressure, and seepage pressure at different positions of the tunnel-slope system in the process of tunnel excavation under the condition of rainfall. The results show that the slope instability caused by rainfall infiltration is gradual. At the beginning of rainfall, the rainfall infiltration has little effect on the stability of the tunnel-slope system and then gradually increases with the continuous rainfall. Finally, the slope surface is uneven, and the phenomenon of gully and surface flow is serious. The foot of slope moves back continuously, resulting in overall collapse. Moreover, during the process of tunnel excavation, the cracks on the tunnel vault of the unburied tunnel lining develop in quadratic along the tunnel excavation direction, and the closer to the excavation section, the larger the collapse range. Finally, there is an integral collapse of the vault of tunnel excavation section. In addition, variation laws of parameters in the tunnel-slope system also provide an important explanation for the hysteresis of the stability failure of the tunnel-slope system. The results have important guiding significance for the stability of the tunnel-slope system during construction.